Is sleep-related attentional bias due to sleepiness or sleeplessness? - Spiegelhalder, K; Espie, C; Riemann, D (2009)
Sleep-related attentional bias is a well-documented finding in patients with primary insomnia. To address the question of whether attentional preference for sleep-related stimuli is due to sleepiness (as measured by the Stanford Sleepiness Scale; SSS) or sleeplessness (as measured by the Pittsburgh Sleep Quality Index; PSQI) we investigated 105 non-clinical participants with two attentional bias tasks, an emotional Stroop task and a newly introduced mixed-modality task. The emotional Stroop task revealed significant positive linear relationships between sleep-related attentional bias and both poor sleep quality and sleepiness. Additionally, we found a significant negative interaction effect between these two variables on the cognitive bias. This means that attentional bias scores are reduced when poor sleep quality is associated with high sleepiness and high sleep quality is associated with low sleepiness. We did not find any significant result in the mixed-modality task. The results suggest that sleep-related attentional bias can be elicited by both sleepiness and sleeplessness.